Hak dan Kewajiban Peserta Magang : Perlindungan Hukum yang Harus Diketahui - Haris, Akmal; Mahendra, Rayhan Nizam; Firdausi, Muhammad Rafli; Lovina Manalu, Sherlin (UNIVERSITAS SERAMBI MEKKAH, 2025)
The internship program is a practical learning tool that aims to provide work experience to interns, as well as support the development of their skills in the professional world. However, in practice, there is often an imbalance between the rights and obligations of apprentices, which can have an impact on their legal protection. This article comprehensively discusses the rights that apprentices have, such as the right to adequate compensation, occupational health and safety protection, and the right to receive quality learning in accordance with the objectives of the internship program. In addition, the obligations of interns, such as complying with company regulations, maintaining the confidentiality of information, and carrying out their duties responsibly, are also reviewed as part of their ethical and professionalism responsibilities. This article highlights the importance of understanding legal protection that apprentices must know, including regulations that apply in Indonesia, such as Law Number 13 of 2003 concerning Employment, Minister of Manpower Regulation No. 6 of 2020 concerning the Implementation of Domestic Apprenticeship Programs, and other relevant regulations. With good understanding, interns can protect themselves from potential exploitation, ensure their rights are fulfilled, and undergo an internship experience that is beneficial and in accordance with the law. This research aims to provide guidance to apprentices, educational institutions and companies in creating a fair, ethical and productive apprenticeship ecosystem.